High frequency of A2143G mutation in clarithromycin-resistant Helicobacter pylori isolates recovered from dyspeptic patients in Iran - Amin T Abadi; Tarang Taghvaei; Ali Ghasemzadeh; Ashraf M Mobarez (The Saudi Journal of Gastroenterology, 2011)
Background/Aim: Resistance to clarithromycin in H. pylori isolates is accepted as a main cause of treatment failure in developing countries. We aimed to determine the prevalence of clarithromycin-resistant strains isolated from dyspeptic patients in northern Iran, furthermore we aimed to assess the relationship between clinical outcomes of infection with point mutations. Materials and Methods: A total of 147 consecutive patients infected with H. pylori were included for determining the status of resistant H. pylori strains. With upper gastroscopy, three antral biopsies were taken from each patient, first section for rapid urea test, second for pathology and third section was used for bacterial culture in microbiologic lab. The antimicrobial susceptibility tests in this examination were agar dilution, in accordance with clinical and laboratory standards institue guidelines. Restriction fragment length polymorphism-PCR (RFLP-PCR) method was applied to determine the frequency of point mutations in 23s rRNA gene. Statistical analysis was performed using SPSS software (15.0) (SPSS, Inc., Chicago, Ill). Chi-square and Fisher′s exact tests were applied to our analysis. A P value less than 5% was considered as statistically significant. Results: Our results showed that there was no point mutation in clarithromycin-susceptible strains of H. pylori. Conclusion: The important findings in our study indicate that A2143G is the most prevalent point mutation (30/32: 93.7%) attributed in clarithromycin resistance among the H. pylori strains. The current study concluded that clarithromycin could still be involved in the empirical treatment of H. pylori infection, although a high frequency of A2143G mutation may increase the concerns regarding treatment failure.